2018
DOI: 10.1590/1981-22562018021.180050
|View full text |Cite
|
Sign up to set email alerts
|

The double vulnerability of elderly caregivers: multimorbidity and perceived burden and their associations with frailty

Abstract: Objective: To identify if multimorbidity and burden are associated with a greater likelihood of frailty in elderly caregivers of other elderly persons within the family context. Method: 148 elderly caregivers caring for other elderly persons [M=69.7 (±7.0) years old] were recruited using a criterion of convenience in public and private health services in the city of Campinas and surrounding areas. Information was gathered about socio-demographic context, context of care, physical health, care burden using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
1
18
0
4
Order By: Relevance
“…Similar results were identified in an investigation carried out with 148 elderly caregivers in the city of Campinas (SP), which aimed to assess the multimorbidity, perceived overload and frailty of all interviewees. As a result, they obtained that 42.5% of the elderly caregivers also scored on reduced physical activity (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were identified in an investigation carried out with 148 elderly caregivers in the city of Campinas (SP), which aimed to assess the multimorbidity, perceived overload and frailty of all interviewees. As a result, they obtained that 42.5% of the elderly caregivers also scored on reduced physical activity (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in a survey conducted with elderly caregivers in the city of Campinas (SP). Of the 148 respondents, 46.0% were pre-fragile according to the criteria of the phenotype proposed by Linda Fried (20) .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in Brazil with 148 older caregivers of older adults recruited from healthcare services investigated the occurrence of frailty in four groups based on the presence/absence of multimorbidity and high or low care-related burden. The prevalence of pre-frailty and frailty was 46% and 35.1%, respectively, and the authors found a greater chance of frailty only in the group of caregivers with multimorbidity, regardless of care-related burden 13 .…”
Section: Introductionmentioning
confidence: 92%
“…(2010) found that caregivers had a high risk of developing frailty. Those caregivers who care for a person with Alzheimer's disease and experience multimorbidity and a high burden have a higher risk of developing frailty (Alves et al., 2018; de Peretti & Villars, 2015). With regard to spousal caregivers, Potier et al.…”
Section: Introductionmentioning
confidence: 99%